2021
DOI: 10.1353/ajm.2021.0000
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric convex sets with minimal Gaussian surface area

Abstract: Let Ω ⊆ R n+1 have minimal Gaussian surface area among all sets satisfying Ω = −Ω with fixed Gaussian volume. Let A = A x be the second fundamental form of ∂Ω at x, i.e., A is the matrix of first order partial derivatives of the unit normal vector at x ∈ ∂Ω. For any. Let A 2 be the sum of the squares of the entries of A, and let A 2→2 denote the 2 operator norm of A.It is shown that if Ω or Ω c is convex, and if eitherthen ∂Ω must be a round cylinder. That is, except for the case that the average value of A 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…We estimate the right-hand-side of (22) in the following way. We estimate the first term by Young's inequality…”
Section: Notation and Set-upmentioning
confidence: 99%
See 3 more Smart Citations
“…We estimate the right-hand-side of (22) in the following way. We estimate the first term by Young's inequality…”
Section: Notation and Set-upmentioning
confidence: 99%
“…We mention also a somewhat similar result by Latala and Oleszkiewicz [26,Theorem 3] who proved that the symmetric strip minimizes the Gaussian perimeter weighted with the width of the set among convex and symmetric sets with volume constraint. For the standard perimeter the problem is more difficult as a simple energy comparison shows (see [22]) that when the volume is exactly one half, the two-dimensional disk and the three-dimensional ball have both smaller perimeter than the symmetric strip in dimension two and three, respectively. Similar difficulty appears also in the isoperimetric problem on sphere for symmetric sets, where it is known that the union of two spherical caps does not always have the smallest surface area (see [4]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the curve case, Guang [Gua18] proved that any smooth embedded 1-dimensional λ-hypersurface (or λ-curve) is either a straight line or a circle if λ ≥ 0, which generalized Abresch and Langer's result. For the higher dimensional case, Heilman [Hei17] proved that convex n-dimensional λhypersurfaces are generalized cylinders. However, when λ < 0, Chang [Cha17] showed that for certain λ < 0, there are some closed embedded mean convex λ-curves other than circles.…”
Section: Introductionmentioning
confidence: 99%